Acetaminophen poisonings in Chilean healthcare settings: a 20-year story that does not end - Sanhueza-Aroca, Tamara; Verdugo-Silva, Samuel; Olate-Fica, Erwin; Rivas, Luisa; Muller-Ramirez, Claudio (Nepal Journal of Epidemiology, 2021)
Background: Acetaminophen (Paracetamol) is one of the most used and prescribed anti-inflammatory and analgesic drugs worldwide. It has become one of the main drugs related to accidental and intentional overdoses in many countries, including Chile. The objective of this work was to characterize acetaminophen poisonings occurred in Chile between the years 2001 and 2020. Methods: A retrospective study of acetaminophen poisonings among patients who were hospitalized in Chilean public and private hospitals was carried out between the years 2001 and 2020. Data was obtained from the Medical Outcome Statistical Report database. Inclusion criteria were cases of patients who were admitted into either public or private healthcare settings with diagnosis of acetaminophen poisoning according to the WHO ICD-10. Statistical analyses were run to establish associations between variables selected in the study. Results: A total of 2,929 cases were included in the study. 77 % of the cases corresponded to female patients (p<0.05). Patients’ age range went from 0 to 81 years old. Adolescents and young adults resulted more involved in reported cases during the 2001-2020 period (p<0.001). During the first period of the study, accidental poisonings were more commonly reported, however in the recent years intentional cases increased their occurrence, especially among female patients (p<0.05). A multivariate logistic regression model considered as statistically significant (p<0.05) the interaction between the variables age, gender and year of the event. Conclusion: The present study identified a large number of acetaminophen poisonings reported in Chile during the 2001-2020 period. Cases were characterized including patients’ gender, age, and poisoning intent. Health authorities should consider these findings as an opportunity to improve public health associated with the use and misuse of over-the-counter drugs, including acetaminophen